2019
DOI: 10.1177/0967391119880046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alkali treatment on mechanical properties of jute fiber-reinforced partially biodegradable green composites using epoxy resin matrix

Abstract: In this work, partially biodegradable green composites have been developed with the help of compression molding technique. Jute fibers were selected as a reinforcement and epoxy resin as matrix material. The influence of alkali treatment on various mechanical properties of jute/epoxy composites was investigated, with concentrations ranging from 1%, 3%, 5%, 7%, and 9% NaOH solution. Various test results indicate that with an increase in concentration, tensile and flexural strength increases up to 5% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…It also improved fibre-matrix adhesion, which improved mechanical qualities. In the same way, a corresponding result was accomplished with jute/epoxy composite [65][66][67]. Figures 7 and 8 show SEM micrographs of biotex flax/PLA reinforced epoxy hybrid nanocomposites with Al2O3 and MgO nanofiller.…”
Section: Scanning Electron Microscope (Sem) Failure Analysismentioning
confidence: 70%
See 2 more Smart Citations
“…It also improved fibre-matrix adhesion, which improved mechanical qualities. In the same way, a corresponding result was accomplished with jute/epoxy composite [65][66][67]. Figures 7 and 8 show SEM micrographs of biotex flax/PLA reinforced epoxy hybrid nanocomposites with Al2O3 and MgO nanofiller.…”
Section: Scanning Electron Microscope (Sem) Failure Analysismentioning
confidence: 70%
“…It also improved fibre-matrix adhesion, which improved mechanical qualities. In the same way, a corresponding result was accomplished with jute/epoxy composite [65][66][67].…”
Section: Impact Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Partially degradable alkali treated jute/epoxy based green composite, made by compression molding technic, was developed with different ranging NaOH concentration. This study revealed that successive alkali surface treatment improved the compatibility of jute fiber and epoxy matrix and effective stress transfer between the fibers and matrix [28]. Degradation is a process of breakdown of chemical particles by a biological environment.…”
Section: Jute Based Bio-compositesmentioning
confidence: 89%
“…The impact strength of PLA composite was 26% higher at higher fiber loading compared to treated fibers in it. A considerable decrease in impact strength of jute/PLA composite after surface modification whereas flexural properties are found to be increased [24,28,26].…”
Section: Impact Propertiesmentioning
confidence: 95%